Confinement degradation and plasma loss induced by strong sawtooth crashes at W7-X. (13th October 2021) - Zanini, M.; Buttenschön, B.; Laqua, H.P.; Thomsen, H.; Stange, T.; Brandt, C.; Braune, H.; Brunner, K.J.; Dinklage, A.; Gao, Y.; Hirsch, M.; Höfel, U.; et al.
Abstract: Sawtooth-like crashes were observed during electron cyclotron current drive experiments for strikeline controls at the optimised superconducting stellarator Wendelstein 7-X (W7-X). The majority of the crashes did not have a relevant impact on plasma performance. However, a limited number of events, characterised by a large plasma volume affected by the instability, have been related to a strong deterioration performance and even to the premature termination of the plasma. The hot plasma core expelled during these sawtooth crashes can reach the plasma edge, where plasma surface interaction can occur and impurities can be released. The x-ray tomography shows a strong radiation increase starting from the edge and moving towards the inner plasma regions. This results in the cooling down and shrinking of the plasma, which eventually leads to a poor coupling of the ECRH to the electrons, that can in turn result in a plasma loss. A relation between the size and amplitude of the sawtooth crashes and the impurity increase is reported.